Research on Optimization of Key Areas of Drainage Borehole Sealing in Ultrathick Coal Seam. (10th March 2021) - Guo, Xin; Xue, Sheng; Li, Yaobin; Zheng, Chunshan; Xie, Linfang
Abstract : Gas drainage is an important means of gas control. The influence of the key position of the sealing hole on gas drainage was studied by theoretical and numerical simulation combined with field measurement to solve low gas concentration in gas predrainage boreholes in coal mines of China. By analyzing the distribution of cracks around the boreholes and the law of air leakage and simulating the drainage effect of different sealing areas (8 m, 12 m, and 16 m), it was proposed that the key position of the sealing hole should be in the prepeak stress concentration area. According to the actual situation of Baode Mine, the sealing test scheme of different sealing areas was put forward, and the field test was carried out to obtain the key sealing area of gas predrainage boreholes in Baode Mine. Research shows that when the sealing area is 8–16 m, the average gas concentration is 63.57%, and the average pure gas flux is 0.408 m 3 /min. The sealing effect of this area is better, with fewer cracks, than that of the existing sealing area, effectively preventing gas leakage and increasing the gas concentration and gas scalar.